RICHARD ROLLE'S LATIN PSALTER IN CENTRAL EUROPEAN MANUSCRIPTS. - VAN DUSSEN, MICHAEL (Medium Aevum, 2018)
The article provides an analysis of Richard Rolle's Latin Psalter commentary. It mentions that copying of the remainder of the commentary was executed in two stages, by two separate scribes like restricting himself exclusively to brief interlinear glosses of particular words or phrases. It mentions that in case of continental manuscripts, there has been a dominant interest in the Carthusian participation in circulating Rolle's texts.